2015
DOI: 10.1186/s12929-014-0108-9
|View full text |Cite|
|
Sign up to set email alerts
|

EpCAM aptamer mediated cancer cell specific delivery of EpCAM siRNA using polymeric nanocomplex

Abstract: BackgroundEpithelial cell adhesion molecule (EpCAM) is overexpressed in solid tumors and regarded as a putative cancer stem cell marker. Here, we report that employing EpCAM aptamer (EpApt) and EpCAM siRNA (SiEp) dual approach, for the targeted delivery of siRNA to EpCAM positive cancer cells, efficiently inhibits cancer cell proliferation.ResultsTargeted delivery of siRNA using polyethyleneimine is one of the efficient methods for gene delivery, and thus, we developed a novel aptamer-PEI-siRNA nanocomplex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…Subramanian et al . reported that, by conjugating epithelial cell adhesion molecule (EpCAM) aptamer to PEI-siEp (siRNA) complex, specific silencing of EpCAM was achieved and cancer cell proliferation was selectively inhibited [71]. Another study also reported VEGF-targeted siRNA delivery by synthesizing bioreducible PEI (SS-PEI) polymer for treating liver cancer in vivo .…”
Section: Polymeric Nanoparticles In Sirna Deliverymentioning
confidence: 99%
“…Subramanian et al . reported that, by conjugating epithelial cell adhesion molecule (EpCAM) aptamer to PEI-siEp (siRNA) complex, specific silencing of EpCAM was achieved and cancer cell proliferation was selectively inhibited [71]. Another study also reported VEGF-targeted siRNA delivery by synthesizing bioreducible PEI (SS-PEI) polymer for treating liver cancer in vivo .…”
Section: Polymeric Nanoparticles In Sirna Deliverymentioning
confidence: 99%
“…In this regard, several shortened aptamers have been proposed with different analytes (Gopinath et al 2006a), as smaller aptamers perform better as chimeras because longer aptamers may undergo degradation. In recent years, there has been an increasing interest in the applications of aptamer chimeras in the field of therapeutics Rohde et al 2015;Subramanian et al 2015;Wang et al 2015;Diao et al 2016). Rohde et al (2015) demonstrated a transferrin receptor and microRNA aptamer chimera (mir-126) that promoted sprouting of endothelial cells and suppressed recruitment of breast cancer cells.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%
“…Rohde et al (2015) demonstrated a transferrin receptor and microRNA aptamer chimera (mir-126) that promoted sprouting of endothelial cells and suppressed recruitment of breast cancer cells. An aptamersiRNA polymeric nanocomplex was designed for targeting epithelial cell adhesion molecules, which are overexpressed in solid tumors (Subramanian et al 2015), and Wang et al (2015) used the aptamer-siRNA chimera to silence survivin in cancer cells and enhance the effect of doxorubicin, even when used in small amounts. Very recently, using an antiprostate specific membrane antigen aptamer-siRNA chimera, Diao et al (2016) specifically controlled the growth of a prostate tumor.…”
Section: Aptamer-based Chimerasmentioning
confidence: 99%
“…Cellular uptake of the complex was evaluated in vitro by flow cytometry and fluorescent microscopy. Inhibition of cancer cell proliferation was evaluated by an MTT assay [110]. …”
Section: Aptamer-nanoparticles Systemsmentioning
confidence: 99%